ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS IV UPT SDN 22 BINAMU - Nurfarezkyanti; Latri; Bhakti Prima Findiga Hermuttaqien (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the Kurikulum Merdeka (Independent Curriculum) in the subject of Pancasila Education for fourth-grade students at UPT SDN 22 Binamu. The research employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The informants in this study consist of the school principal and subject teachers. The findings indicate that the implementation of the Kurikulum Merdeka has been carried out fairly well. This is evidenced by the adaptation of teaching materials and the application of contextual learning approaches. However, several obstacles were identified during its implementation, such as limited teacher understanding of the curriculum's concepts, lack of ongoing training, and inadequate supporting infrastructure. In general, teachers responded positively to the implementation of the Kurikulum Merdeka, as it provides flexibility in the design and execution of learning activities. Based on these findings, the study recommends continuous teacher training and improved educational facilities to support the successful implementation of the Kurikulum Merdeka.